Supplemented αMEM/F12‐based medium enables the survival and growth of primary ovarian follicles encapsulated in alginate hydrogels. Issue 12 (15th July 2013) - Tagler, David; Makanji, Yogeshwar; Anderson, Nicholas R.; Woodruff, Teresa K.; Shea, Lonnie D.
ABSTRACT Hydrogel‐encapsulating culture systems for ovarian follicles support the in vitro growth of secondary follicles from various species including mouse, non‐primate human, and human; however, the growth of early stage follicles (primary and primordial) has been limited. While encapsulation maintains the structure of early stage follicles, feeder cell populations, such as mouse embryonic fibroblasts (MEFs), are required to stimulate growth and development. Hence, in this report, we investigated feeder‐free culture environments for early stage follicle development. Mouse ovarian follicles were encapsulated within alginate hydrogels and cultured in various growth medium formulations. Initial studies employed embryonic stem cell medium formulations as a tool to identify factors that influence the survival, growth, and meiotic competence of early stage follicles. The medium formulation that maximized survival and growth was identified as αMEM/F12 supplemented with fetuin, insulin, transferrin, selenium, and follicle stimulating hormone (FSH). This medium stimulated the growth of late primary (average initial diameter of 80 µm) and early secondary (average initial diameter of 90 µm) follicles, which developed antral cavities and increased to terminal diameters exceeding 300 µm in 14 days. Survival ranged from 18% for 80 µm follicles to 36% for 90 µm follicles. Furthermore, 80% of the oocytes from surviving follicles with an initial diameter of 90–100 µm underwent germinal vesicle breakdown (GVBD), and the percentage of metaphase II (MII) eggs was 50%. Follicle/oocyte growth and GVBD/MII rates were not significantly different from MEF co‐culture. Survival was reduced relative to MEF co‐culture, yet substantially increased relative to the control medium that had been previously used for secondary follicles. Continued development of culture medium could enable mechanistic studies of early stage folliculogenesis and emerging strategies for fertility preservation. Biotechnol. Bioeng. 2013;110: 3258–3268. © 2013 Wiley Periodicals, Inc.